Development and Validation of a Cognitive Behavioral Spiritual Counseling Model for Enhancing Spiritual Well-Being among Individuals with Drug Addiction - Supriyanto, Agus; Hendiani, Nurlita; Athar, Samia; Direja, Syaharani Maulia (Indonesian Journal of Learning Education and Counseling, 2026)
Drug addiction negatively impacts individuals’ quality of life, particularly in terms of spiritual well-being, creating a gap between empirical conditions and the ideal expectation of religious closeness. This gap increases the risk of relapse and highlights the urgency of counseling services that integrate not only cognitive and behavioral aspects but also spirituality, which is often neglected in current approaches. This study aims to develop and validate a Cognitive Behavioral Spiritual (CBT-S) counseling model to enhance the spiritual well-being of clients with addictions. This research employed a research and development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Participants included 117 drug-addicted clients to assess spiritual well-being, along with three experts and five addiction counseling practitioners involved in the validation process. Data were analyzed using descriptive qualitative methods and interrater reliability through Cohen’s Kappa. The findings indicate that clients’ spiritual well-being remains in low to moderate categories, forming the basis for developing the CBT-S model. The results show that the CBT-S counseling model is feasible and reliable for improving spiritual well-being. The model offers a novel framework with stages of Al-Aajis, Al-Khathir, Hadith An-Nafs, Al-Hamm, and Al-‘Azm, integrating spiritual values by involving God throughout the counseling process.